Mild Inflammatory Profile without Gliosis in the c-Rel Deficient Mouse Modeling a Late-Onset Parkinsonism - Porrini, Vanessa; Mota, Mariana; Parrella, Edoardo; Bellucci, Arianna; Benarese, Marina; Faggi, Lara; Tonin, Paolo; Spano, Pier F.; Pizzi, Marina (Frontiers in Aging Neuroscience, 2017)
The impact of neuroinflammation and microglial activation to Parkinson’s disease (PD) progression is still debated. Post-mortem analysis of PD brains has shown that neuroinflammation and microgliosis are key features of end-stage disease. However, microglia neuroimaging studies and evaluation of cerebrospinal fluid cytokines in PD patients at earlier stages, do not support the occurrence of a pronounced neuroinflammatory process. PD animal models recapitulating the motor and non-motor features of the disease, and the slow and progressive neuropathology, can be of great advantage in understanding whether and how neuroinflammation associates with the onset of symptoms and neuronal loss. We recently described that 18-month-old NF-κB/c-Rel deficient mice (c-rel-/-) develop a spontaneous late-onset PD-like phenotype encompassing L-DOPA-responsive motor impairment, nigrostriatal neuron degeneration, α-synuclein and iron accumulation. To assess whether inflammation and microglial activation accompany the onset and the progression of PD-like pathology, we investigated the expression of cytokines (Il1b, Il6) and microglial/macrophage activation markers (Fcgr3, Mrc1, Ym1, Arg,1, Trem2), together with microglial (Iba1) and astrocyte (GFAP) immunolabelling, in the substantia nigra (SN) of c-rel-/- mice, at premotor (4- and 13-month-old) and motor phases (18-month-old). By quantitative real-time RT-PCR we found increased M2c microglial/macrophage markers expression (Mrc1 and Arg1) in 4-month-old c-rel-/- mice. M2-type transcription dropped down in 13-month-old c-rel-/- mice. At this age, the pro-inflammatory Il1b, but not Il6 or the microglia-macrophage M1-polarization marker Fcgr3/CD16, increased when compared to wild-type. Furthermore, no significant variation in the transcription of inflammatory and microglial/macrophage activation genes was present in 18-month-old c-rel-/- mice, that display motor dysfunctions and dopaminergic neuronal loss. Immunofluorescence analysis of Iba1-positive cells in the SN revealed no sign of overt microglia activation in c-rel-/- mice at all the time-points. MRC1-Iba1-positive cells were identified as non-parenchymal macrophages in 4-month-old c-rel-/- mice. Finally, no sign of astrogliosis was detected in the SN of the diverse animal groups. In conclusion, this study supports the presence of a mild inflammatory profile without evident signs of gliosis in c-rel-/- mice up to 18 months of age. It suggests that symptomatic PD-like phenotype can develop in the absence of concomitant severe inflammatory process.